Acute aseptic meningitis during isotretinoin treatment for nodular acne solely presenting with headache: case report and brief review of the literature. (1st February 2019) - Chalimou, Ioanna; Krilis, Antonios; Anastopoulou, Garifallia G.; Braun, Heike; Vikelis, Michael; Makridou, Alexandra; Makris, Nicolaos; Argyriou, Andreas A.
Abstract: Purpose/aim : We describe, in detail, the first case of isotretinoin-induced aseptic meningitis. A brief summary of the literature on drug-induced aseptic meningitis (DIAM) is also presented. Materials and methods : A 20-year old female patient with probable (Naranjo adverse reaction probability score of 7) DIAM during treatment with isotretinoin therapy for nodular acne solely, presenting with headache. Pseudotumor cerebri was appropriately ruled-out. Results : Summary of data altogether lead us suggest that isotretinoin triggered DIAM, possible due to a delayed hypersensitivity mechanism type III or IV. Conclusion : We highlight a quite uncommon cause of DIAM that may be increasing in frequency due to the current increasing use of isotretinoin against nodular acne.